Implementation of In-Depth Learning Methods in Christian Religious Education Learning for Grade XII - Lien Meilan; Karolina Karolina; Ellysa Juang Agusti (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid advancement of educational paradigms in the digital era requires teachers to implement innovative instructional approaches that promote meaningful and student-centered learning. This study aims to explore the implementation of the Deep Learning method in Christian Religious Education (CRE) learning for Grade XII students at SMA Negeri 1 Palangka Raya and examine its impact on students' critical thinking, spiritual growth, and learning engagement. This research employed a qualitative descriptive approach involving Christian Religious Education teachers and Grade XII students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation studies, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the Deep Learning method successfully transformed conventional teacher-centered instruction into meaningful learning experiences characterized by inquiry, collaboration, reflection, contextual problem-solving, and authentic assessment. The implementation of this method significantly enhanced students' critical thinking abilities, communication skills, collaborative competence, spiritual awareness, and active participation in classroom activities. Students demonstrated greater ability to relate biblical teachings to contemporary social issues and personal experiences. Despite challenges such as differences in students' readiness and limited instructional time, continuous teacher facilitation effectively supported successful implementation. Therefore, the Deep Learning method represents an effective pedagogical approach for improving the quality of Christian Religious Education and supporting the objectives of the Merdeka Curriculum in Indonesian secondary education.